Global Changes in Optic Nerve Head Gene Expression after Exposure to Elevated Intraocular Pressure in a Rat Glaucoma Model - Johnson, Elaine C. (2007)
PURPOSE: In glaucoma, the optic nerve head (ONH) is the likely site of initial injury and elevated intraocular pressure (IOP) is the best-known risk factor. This study determines global gene expression changes in the pressure-injured ONH. METHODS: Unilateral sustained IOP elevation (glaucoma, n = 46) or optic nerve transection (n = 10) was produced in rats. ONHs were removed, and the retrobulbar optic nerves were graded for degeneration. Gene expression in the glaucomatous ONH with extensive injury was compared with that in the fellow ONH (n = 6/group), by using cDNA microarrays. Data from 12 arrays were normalized, significant differences in gene expression determined, and significantly affected gene classes identified. For the remaining ONH, grouped by experimental condition and degree of injury, quantitative reverse transcriptase-PCR (qPCR) and ANOVA were used to compare selected message levels. RESULTS: Microarray analysis identified more than 2000 significantly regulated genes. For 225 of these genes, the changes were greater than twofold. The most significantly affected gene classes were cell proliferation, immune response, lysosome, cytoskeleton, extracellular matrix, and ribosome. A 2.7-fold increase in ONH cellularity confirmed glaucoma model cell proliferation. By qPCR, increases in levels of periostin, collagen VI, and transforming growth factor β1 were linearly correlated to the degree of IOP-induced injury. For cyclinD1, fibulin 2, tenascin C, TIMP1, and aquaporin-4, correlations were significantly nonlinear, displaying maximum change with focal injury. CONCLUSIONS: In the ONH, pressure-induced injury results in cell proliferation and dramatically altered gene expression. For specific genes, expression levels were most altered by focal injury, suggesting that further array studies may identify initial, and potentially injurious, altered processes.